Capturing andrographis paniculata herbal extract on gold nanoparticle to evaluate antimicrobial activity - Nurulshima Binti Razalli (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This research is a way to accomplish the antimicrobial study towards different types of gram bacteria; in this project the microorganisms used are Escherichia coli and Bacillus sp, by Andrographis paniculata conjugated Gold Nanoparticle (GNP). The ease of capturing on GNP and their affinity for binding biological molecules makes them attractive participants to study. In fact, they have so many advantages in conjugation with herbal plant extract. In this project, first and foremost, it was be able to prepare the A. paniculata herbal extract conjugated with GNP to be used as broad spectrum in antimicrobial activity. Other than that, this study also intends to analyze the captured molecules obtained from A. paniculata on the GNP. Besides that, the herbal extract conjugated GNP has been studied due to their effects on antimicrobial activity. The conjugation of herbal extract with GNP has been evaluated by characterization method such as Fourier Transmission Infrared (FTIR) Spectroscopy, Screening Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM). The antibiotic such as ampicillin has been used as the positive control and water as negative control on antimicrobial study and the effects have been tested using antimicrobial assay which is disc diffusion for both microorganisms involved. The inhibition zone has been measured for disc diffusion for both microorganisms were in range of 0.6 cm to 0.9 cm for plant extract. However, plant extract conjugated GNPs were in between of 0.8 cm to 1.1 cm which is larger than without conjugation. This shows that herbal extract conjugated GNP gives out the best result.